Exploring the complexity, treatment challenges, and outcomes in pediatric nodular lymphocyte predominant Hodgkin lymphoma: a perspective from a low–middle-income country - Madney, Youssef; Abdalla, Amr; Ahmed, Soha; Romeih, Marwa; Fikry, Sally; Mohammed, Engy; Taha, Hala; Zaghloul, Mohamed; Attia, Eman (Frontiers in Oncology, 2024)
BackgroundIn children, nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is an uncommon subtype of Hodgkin lymphoma. Given the lack of data on the best chemotherapy regimen, there is a knowledge gap in best management.MethodsThis retrospective study included all pediatric patients with NLPHL diagnosed and treated at the Children’s Cancer Hospital, Egypt (2007–2018). We analyzed the clinical characteristics, and treatment outcome according to disease stage (early and advanced), treatment strategy (doxorubicin, bleomycin, vinblastine, and dacarbazine [ABVD] or rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone [R-CHOP] and explored the prognostic factors for progression-free survival.ResultsThe median age at diagnosis was 12 years; 40 (68%) patients had early-stage disease, and 19 (32%) had advanced-stage disease. The median follow-up was 70 months; the 5-year EFS and OS were 75% and 97%, respectively. The 5-year EFS was 78% for early-stage disease and 60% for advanced-stage disease; the 5-year OS was 100% for early-stage disease and 88% for advanced-stage disease. The patients who underwent R-CHOP had a better 3-year EFS (100%) compared with those who underwent ABVD (65%) regimen (P = 0.01). Seventeen (25%) patients relapsed: 9/40 (22%) had early-stage disease, and 8/19 (42%) had advanced-stage disease. Splenic involvement, mediastinal disease, extranodal disease, and slow early response were independent predictors of relapse risk.ConclusionPediatric patients with early-stage NLPHL have an excellent prognosis, with a 5-year OS of 100%. However, those with advanced stages had a high relapse rate. R-CHOP was associated with a better response and relapse-free rate than ABVD.